Robot-assisted pulmonary lobectomy - Dolezel, J; Vlcek, P (Bratislavske lekarske listy, 2008)
The authors present their first experience and the results of robot-assisted pulmonary lobectomies. The paper reports on the placement of the working channels, auxiliary minithoracotomies, the patient's position, the positions of the four-arm body of the da Vinci robotic system, and particularly the technique of lobectomy. In our institution, 4 robot-assisted lobectomies were performed in two women and two men (aged 45, 52, and 57, 67 years, respectively). The vessels were ligated mechanically with the use of the robot. An auxiliary minithoracotomy of a length of 5 cm was performed in the fifth intercostal area posterolaterally. The lower lobectomy was performed three times left and once right. The surgery was always supplemented with mediastinal lymphadenectomy. No serious complications were observed during the surgery or in the postoperative period. Robot-assisted lobectomy is a safe method of pulmonary resection in the early stages of bronchogenic carcinoma (Ia, Ib); it ensures a faster convalescence of the patient compared with open surgery (Ref. 14).
Keywords: lymfadenektomie; Female; pneumektomie; Mediastinum; ženské pohlaví; nádory plic; Robotics; lidé; mediastinum; Lymph Node Excision; Pneumonectomy; robotika; Male; Aged; Lung Neoplasms; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans